Conformational similarities in the beta-ionone ring region of the rhodopsin chromophore in its ground state and after photoactivation to the metarhodopsin-I intermediate. - Spooner, P; Sharples, J; Goodall, S; Seedorf, H; Verhoeven, M; Lugtenburg, J; Bovee-Geurts, P; DeGrip, W; Watts, A (2003)
High-resolution solid-state NMR methods have been used to analyze the conformation of the chromophore in the late photointermediate metarhodopsin-I, from observation of (13)C nuclei introduced into the beta-ionone ring (at the C16, C17, and C18 methyl groups) and into the adjoining segment of the polyene chain (at C8). Bovine rhodopsin in its native membrane was also regenerated with retinal that was (13)C-labeled close to the 11-Z bond (C20 methyl group) to provide a reporter for optimizing and quantifying the photoconversion to metarhodopsin-I. Indirect photoconversion via the primary intermediate, bathorhodopin, was adopted as the preferred method since approximately 44% conversion to the metarhodopsin-I component could be achieved, with only low levels (approximately 18%) of ground-state rhodopsin remaining. The additional photoproduct, isorhodopsin, was resolved in (13)C spectra from C8 in the chain, at levels of approximately 38%, and was shown using rotational resonance NMR to adopt the 6-s-cis conformation between the ring and the polyene chain. The C8 resonance was not shifted in the metarhodopsin-I spectral component but was strongly broadened, revealing that the local conformation had become less well defined in this segment of the chain. This line broadening slowed rotational resonance exchange with the C17 and C18 ring methyl groups but was accounted for to show that, despite the chain being more relaxed in metarhodopsin-I, its average conformation with respect to the ring was similar to that in the ground state protein. Conformational restraints are also retained for the C16 and C17 methyl groups on photoactivation, which, together with the largely preserved conformation in the chain, argues convincingly that the ring remains with strong contacts in its binding pocket prior to activation of the receptor. Previous conclusions based on photocrosslinking studies are considered in view of the current findings.